Investigating Effects of Growth and Conservatism on Bias of ROI Compared with Internal Rate of Return - Ali Rahmani (Shahid Bahonar University of Kerman, 2015)
The Return on Investment (ROI) is widely regarded as a key measure of firm’s performance. The literature has recognized, mostly, that ROI will not reflect economic profitability. This study takes behavior of ROI as a function of two variables: past growth and accounting conservatism. The studied sample consists of 61 firms listed in the Tehran Stock Exchange, in which the required data for a 5-year-period of 1386-1390 was available. In this study the growth of investment refers to the growth of expenses for advertising and R&D, and conservatism means unconditional conservatism from direct transfer of these expenses to expenditure account. The growth of investment, which may stand at a level higher or lower than a critical value, measured by internal rate of return, may be regarded as moderate or excessive. The hypotheses were tested by the regression model of panel data. The findings showed that in case of conservative accounting, higher growth results in lower level of ROI. Conversely, in case of more conservative accounting, the ROI will increase, provided that new investments grow moderately over the relevant time horizon.